Analysis Of The Influence Of Marketing Mix 7p On Purchasing Decisions At PT Batik Pirukun Makmur - Arif Ramadhan, Irfan; Wahyu Utami, Indah; Ismoyo Buwono, Ringgo (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2024)
The main challenge is faced by PT. Batik Pirukun is the lack of clarity and lack of marketing strategy information about accurate consumer behavior. therefore researchers are interested in knowing consumers reasons decided to make a purchasing decision at PT Batik Pirukun Makmur. With the right marketing strategy, it is hoped that PT Batik Pirukun will become prosperous able to have loyal consumers and consumers get good products desired. This research aims to examine more deeply the implementation of marketing mix strategies. From the analysis carried out by researchers, the following results were obtained: The variables product, price, promotion, place, people, process, physical evidence have a positive and significant effect on purchasing decisions at PT Batik Pirukun Makmur. PT Batik Pirukun Makmur should further improve product quality because this can influence customers in making purchasing decisions and can increase customer satisfaction.